De l’hétérotopie coloniale à la Lebensreform - Camille Auboin (Recherches Germaniques)
In life-reform movements, there were sometimes close ties with the German colonial space. This article will build on texts by the colonial officer and life-reformer Hans Paasche (1881-1920) and aim to analyze colonial space as a “heterotopia” (Michel Foucault). It will four both on the depiction of colonial space by Paasche and on the influence of this colonial heterotopia on Wilhelmine society. Indeed, Paasche’s life-reform ideas were based on a largely fantasized conception of colonial space, ideas through which he sought to reform the way of life in Germany. His hope was that ‘going native’ would in the end ‘regenerate’ the degenerated motherland.